2021
DOI: 10.1016/j.isci.2021.102876
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Kv4.2 potassium channels selectively mediate spatial pattern separation in the dentate gyrus

Abstract: Summary The capacity to distinguish comparable experiences is fundamental for the recall of similar memories and has been proposed to require pattern separation in the dentate gyrus (DG). However, the cellular mechanisms by which mature granule cells (GCs) of the DG accomplish this function are poorly characterized. Here, we show that Kv4.2 channels selectively modulate the excitability of medial dendrites of dentate GCs. These dendrites are targeted by the medial entorhinal cortex, the main source … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 84 publications
(127 reference statements)
0
4
0
Order By: Relevance
“…The critical role of intrinsic excitability in determining dentate gyrus MPP output was also recently highlighted by Zhang et al (2020). Oule et al (2021) identified the potassium channels responsible for dendritic intrinsic excitability in male mice as the Kv4.2 subtype and revealed that these channels are critical for spatial pattern separation.…”
Section: Discussionmentioning
confidence: 83%
“…The critical role of intrinsic excitability in determining dentate gyrus MPP output was also recently highlighted by Zhang et al (2020). Oule et al (2021) identified the potassium channels responsible for dendritic intrinsic excitability in male mice as the Kv4.2 subtype and revealed that these channels are critical for spatial pattern separation.…”
Section: Discussionmentioning
confidence: 83%
“…One possible mechanism by which Shal channels might affect receptor potenWal dynamics locally in the dendrite is to sharpen receptor potenWals through their fast acWvaWon and inacWvaWon kineWcs (18,30,34,35). In hippocampal CA1 pyramidal cell dendrites and granule cell dendrites in the dentate gyrus, the transient A-type potassium currents (encoded by Kv4) have also been reported to inhibit backpropagaWon of acWon potenWals, limit the dendriWc iniWaWon of acWon potenWals and dampen the effect of excitatory dendriWc inputs (36)(37)(38). Thus, in JO neuron dendrites, Shal may be shaping the kineWcs of one receptor potenWal as it develops, and may also modulate any back propagaWon to coordinate with the next cycle of receptor potenWal acWvaWon to sustain acWve oscillaWons.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable evidence has established the role of Kv4.2-mediated A-type K + current in dendritic signaling and synaptic plasticity (Hoffman et al, 1997; Kim et al, 2012, 2019, Kim et al, 2005; Jung et al, 2009; Simkim et al, 2015; Rathour et al, 2016; Carrasquillo et al, 2012; Oule et al, 2021; Hoffman et al, 1997). Inhibition of Kv4.2 mediated outward currents in dendrites have been regarded to amplify synaptic depolarization, but we could not find its amplification effect.…”
Section: Discussionmentioning
confidence: 99%
“…The voltage-gated K + channel Kv4.2, responsible for mediating transient A-type currents (I A ), operates within the subthreshold voltage range to perform various physiological functions. These include the regulation of resting membrane potential (RMP) and action potential (AP) repolarization (Kim et al, 2005) as well as the modulation of synaptic response (Hoffman et al, 1997, Migliore et al, 1999, Johnston et al, 2003, Oule et al, 2021). The graded expression of I A in dendrites acts to constrain the integration and propagation of sub- and suprathreshold voltage signals, including dendritic spikes and back-propagating action potential (b-AP) in the hippocampus (Hoffman et al, 1997, Ramakers and Storm 2002, Johnston et al, 2003, Cai et al, 2004, Losonczy et al, 2006).…”
Section: Introductionmentioning
confidence: 99%